Ultrasonographic approach for measurement of crown rump length of goat fetus - GAIKWAD, S M; DHOBLE, R L; DEOKATE, K R; CHAVAN, S G; MUNDE, V K (The Indian Journal of Animal Reproduction, 2007)
The present study was carried out for the measurement of goat foetal crown rump length(CRL). 40 ewes were synchronized and bred naturally, among which 25 ewes were pregnant. These25 ewes were subjected to foetal crown rump length observations using B-mode real timeultrasonography from day 35 to 70 of gestation. The mean CRL of Osmanabadi ewes were 27 .82 ±0.73 (day 35), 46.35 ± 1.32 (day 42), 65.32 ± I.IS mm (day 49), 82.85 ± 0.88 mm (day 56), 99.66 ± 0.94 mm (day 63) and 117.27 ± 1.12 mm (day 70).
Keywords: Ultrasonography; CRL; Goat